TO EVALUATE THE OUTCOME OF DARNING REPAIR IN OBSTRUCTED INGUINAL HERNIA IN MALE AT CMC HOSPITAL LARKANA. - Muharram Ali Abbasi1 , Abdul Ghani2 , Ehsanullah Malik3 , Nadia Bhatti4 , Sania Bhatti5 , Waqare-Sahar Shah6, (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2022)
ABSTRACT INTRODUCTION: Inguinal Hernia is operated by two methods. One is open and another laparoscopic. Open procedures include Bassini, Modified Bassini, Shouldice, Darning and Lichtenstein. Of them, the commonly performed after hernioplasty is Darning. It is tension free repair commenced from pubic tubercle and ended at pubic tubercle. It approximates inguinal ligament to conjoint tendon. It has better results as compared to others. OBJECTIVE; to evaluate the results of Darning repair in inguinal obstructed hernia in male patients.TYPE OF STUDY: Cross sectional DURATION AND PLACE OF STUDY: This is study of one year done from March 2019 to February 2020 at Chandka Medical College Hospital Larkana. RESULTS: Total 150 patients were selected but only 41 (27.33 %) had symptoms of obstructed inguinal hernia. Type of inguinal was seen in obstructive stage. 38 (93%) were suffering from irreducible indirect inguinal hernia whereas only 3 (7%) were diagnosed as direct inguinal hernia. Postoperative complications of obstructed inguinal hernia are various. 10 (24.39%) patients developed wound infection. 3 (7.31%) had hematoma postoperatively. Recurrence was in 1 (2.4%) patient. No one presented with complain of paresthesia over thigh. CONCLUSION: Darning repair in inguinal hernias is the better techniques s it is cost effective and least recurrent.